Fisheries Management of Julung Julung Fish (Hemiramphus spp) with an Ecosystem Approach in the Waters of Keffing Island, East Seram Regency - Rumakat, Mohammad Ali; Tupamahu, A.; Haruna, Haruna (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The study was conducted in Keffing Island, East Seram Regency with the aim of analyzing indicators of julung-julung management in the fish resource domain in the waters of Keffing Island, East Seram Regency. The emphasis on experimental fishing and the use of the EAFM method is expected to provide a clear picture of the management status of julung-julung in the fish resource domain. Ecosystem Approach to Fisheries Management (EAFM) or can be understood as a concept of balancing socio-economic objectives in fisheries management by considering knowledge, information and uncertainties about biotic, abiotic and human interaction components in aquatic ecosystems through an integrated, comprehensive and sustainable fisheries management. The implementation of EAFM requires a set of indicators that can be used as a monitoring and evaluation tool regarding the extent to which fisheries management has implemented the principles of ecosystem-based management. The results showed that the assessment results of the fish resource domain, where the EAFM indicator showed a Composite Value value of 59.02 with a description of the status of julung fish management is in moderate condition.